(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Displays of karst in calcareous rocks and forming of underground emptinesses in effusive rocks of Armenian highlands have been examined in the article. Broad spreading limestone-dolomite rocks in the mountains of the Minor Caucasus, Armenian Eastern Taurus and Inside Taurus, their considerable dislocation and intensive partition of ranges by deep valleys assist in developing of karst in the highland. In effusive rocks the formation of underground emptinesses are only partially. A lot of emptinesses are formed in them as a result of cooling of lava flow and loss of gas.